Aqueous Pressure Oxidation of Silver-Bearing Cyanide Refractory Concentrates in Acidic Sulfate and Sulfate-Iodide Media - G. Van Weert (The Minerals, Metals and Materials Society, 1994)
Refractory gold ores and auriferous concentrates containing silver tend to form refractory silver jarosites during pressure oxidation. Earlier work with pure Ag2S has shown that the addition of iodine species to the autoclave feed yields cyanide soluble iodargyrite (Agl) instead. Near complete silver extractions from the autoclave product were obtained at a I-/Ag+ ratio of 5 or more. This paper reports on the pressure oxidation and cyanide leaching of two industrial refractory (arseno) pyritic silver-bearing concentrates: 1. from Peru (sulphosalts) and 2. from the USA (pyrite, with acanthite occlusions). While using a I-/Ag+ mol ratio of only 1 in the feed, it has been possible to obtain 98 and 97% Ag extraction from the two autoclave products by cyanide leaching, respectively. This compares to 11 and 54% Ag extraction from the as-received concentrates and 4 and 15% Ag extraction, respectively, after pressure oxidation without KI present. The results of the testwork are discussed in terms of concentrate mineralogy and pressure oxidation conditions.